Tradisi Makawas Pada Kehidupan Sosiokultural Masyarakat Bali Mula - Pertiwi, Natasya; Darmana, I Ketut; Kaler, I Ketut (Humanis; Vol 24 No 4 (2020)DO - 10.24843/JH.2020.v24.i04.p14, 2020)
The community in Sekardadi Village, sub-district Kintamani, district Bangli are the community of Bali Mula which has a variety of activities in a Hindu background which is manifested through religious ceremonies. Religious activitiy that contain traditional values ??expressed through a tradition are makawas. Makawas tradition is one of a series that has important elements in religious ceremonies that are routinely carried out by the Sekardadi village community. The research aims at finding out: (a) how the implementation and mechanism of the makawas tradition in the socio cultural life community of Bali Mula and (b) how the function of the Makawas tradition in the socio cultural life community of Bali Mula in Sekardadi Village. The results showed that makawas tradition was routinely carried out by the Sekardadi village community based on the belief of a mitohistorical in the form of gratitude and blessing. The implementation of makawas tradition starts from preparing all the ceremonial and kawas needs. Then after all the means ceremonial have been prepared, Jero Kubayan began to provide kawas and banten to Ida Sang Hyang Widhi Wasa. Further Pepare distributed the kawas to Pradulu Ulu Apad and krama pengarep. The meaning of religion from makawas tradition is manifestation of the relationship between Ida Sang Hyang Widhi Wasa stated in one of the Tri Hita Karana elements in the form of Prahyangan which means the relationship between humans and God and as a mean for people’s life that is to form a solidarity relationship.